2013
DOI: 10.4236/jep.2013.412160
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Risk Evaluation Method Employing Atmospheric Dispersion Models and GIS

Abstract: This study aims to develop a method for evaluating the environmental risk of harmful chemical substances released from specific sources, using two atmospheric dispersion models and GIS (Geographic Information Systems). In the first stage of evaluation, ADMER was used to conduct a wide-area evaluation which covered the entire area of the evaluation target region. In the second stage, METI-LIS was used to conduct a detailed limited-area evaluation which targeted the vicinity of sources. In this study, incinerato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(30 reference statements)
0
4
0
1
Order By: Relevance
“…Humans are exposed to PCDFs, PCDDs, and PCBs through environmental, occupational contamination, and accidental exposure [2].…”
Section: Exposure To Dioxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans are exposed to PCDFs, PCDDs, and PCBs through environmental, occupational contamination, and accidental exposure [2].…”
Section: Exposure To Dioxinsmentioning
confidence: 99%
“…Among this group of chemicals are dioxins. Dioxins and dioxin-like compounds (DLC) are highly persistent organic pollutants (POPs) that are extremely poisonous and highly resistant to chemical, biological, and photolytic destruction [2]. Polychlorinated dibenzofurans (PCDFs), polychlorinated dibenzodioxins (PCDDs), and dioxin-like polychlorinated biphenyl (DL-PCBs) are the three main categories under which POPs are categorized.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding studies that grasped the behavior of air pollutants using atmospheric dispersion model, there have been many with dioxin as its subject. Some of the representative studies in recent years include that of Sasaki et al [1], Teshima et al [2], Hoa [3], Viel [4], Ripamonti et al [5], Ashworth et al [6], Ishii and Yamamoto [7], Sun et al [8], and Zhang et al [9], in which simulations of the behavior of dioxins in the atmosphere were conducted with incinerators as its generation source. Maantay et al [10], Chen et al [11], Kawashima et al [12], Onofrio et al [13], Zhou et al [14], and Chandra et al [15] conducted simulations of dioxins in the atmosphere.…”
Section: Related Workmentioning
confidence: 99%
“…Among the related studies above, Maantay et al [10] and Viel [4] demonstrated the effectiveness to combine atmospheric dispersion model and GIS to estimate the behavior of dioxins in the atmosphere. Additionally, Ishii et al [7] combined two types of atmospheric dispersion models and GIS to grasp the dispersion conditions of dioxins in both wide-rage and small-range areas with high concentration and proposed a method to evaluate environmental risks.…”
Section: Related Workmentioning
confidence: 99%
“…Ugyanakkor a modellek eredményeinek felhasználói, a döntéshozók és hatóságok felé való kommunikáció szempontjából fontossá vált a terjedési modellek térinformatikai szoftverekbe való integrációja, valamint az eredmények bizonytalanságának becslése a kockázatalapú döntéstámogató rendszerek kiszolgálása érdekében (Ishii and Yamamoto, 2013). Különleges jelentőséget kaptak ezek a szempontok a 2011-es japán földrengés után, amikor a Fukushimából származó radioaktív szennyeződés Japánban komoly környezeti és egészségügyi kockázatokat jelentett, csekély mértékben pedig globálisan is kimutatható volt (Steinhauser et al, 2014).…”
Section: Előzmények éS Motivációunclassified